Simulasi genangan banjir menggunakan data ASTER DEM pada alur Sungai Cilemer - Nuryanto Sasmito Slamet; Sarwono Sarwono (JURNAL SUMBER DAYA AIR, 2016)
The Cilemer River is a river which flowing to Lada Bay in west coast of Pandeglang District, Banten Province. The influence of the tide, the high flood discharges and settlements located at the flood plain has caused flooding every year. In order to understand flood overtopping mechanism and inundation map, numerical model simulation for flood and inundation area were conducted. The numerical model of the river were conducted using cross sectional of the river, result of these simulations were further integrated with Geographical Information System (GIS). The objective of this study is to obtain inundation map area. The input for GIS is a Digital Elevation Model which is obtain from Advanced Spaceborne Thermal Emission and Reflection Radiometer Digital Elevation Model (ASTER DEM). The simulation results shows the capacity of Cilemer River upstream is 210 m3/s while on the downstream segment was only 100 m3/s. Simulation shows with overtopping of the dike of 0,96 m generate 546 Ha of inundation area for 2 year return period of flood discharge. The overtopping of 1,1 m has generated 592 Ha of inundation area for 5 year return period of flood discharge. With overtopping of 1,26 m of 10 year return period flood discharge has caused 682 Ha inundation area, while 2,56 m overtopping has generated 912 Ha inundation area for 25 year return period of flood discharge. Effect of flood control structure on the outlet of bypass has generated 19 cm increase of water level.